2022
DOI: 10.1186/s12936-022-04243-1
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative study on the use and maintenance of long-lasting insecticidal nets (LLINs) in Bouaké (Côte d’Ivoire), 17 months after the last mass distribution campaign

Abstract: Background The use of long-lasting insecticide-treated nets (LLINs) is one of the main malaria prevention method promoted by the World Health Organization (WHO) in Côte d'Ivoire. LLIN-coverage has reached 95% since 2015 and nearly 16 million LLINs were distributed in 2017. Despite these efforts, malaria incidence at the national level remains high (120‰ in 2012 to 164‰ in 2017) although this could be partly explained by increased screening efforts. This study aimed at determining what preventat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The present study indicates that ITNs were washed relatively infrequently in the study sites in PNG, as compared to other studies [19][20][21], with over 90% of ITNs never having been washed in the first 6 months and a median number of washes of 1 (IQR 1-3) at 24 months after distribution. Most people used laundry powder or laundry soap bars to wash the ITNs but only a small percentage (7-8%) resorted to adding bleach.…”
Section: Parameter Exp(b) (95% Ci) Psupporting
confidence: 49%
“…The present study indicates that ITNs were washed relatively infrequently in the study sites in PNG, as compared to other studies [19][20][21], with over 90% of ITNs never having been washed in the first 6 months and a median number of washes of 1 (IQR 1-3) at 24 months after distribution. Most people used laundry powder or laundry soap bars to wash the ITNs but only a small percentage (7-8%) resorted to adding bleach.…”
Section: Parameter Exp(b) (95% Ci) Psupporting
confidence: 49%
“…Generally, social and economic status are two of the factors affecting net handling. A study conducted in Bouaké, Côte d'Ivoire, found that household owners with primary/higher education had better knowledge about how to manage (tuck in on the bed, washing, drying) nets than those who reported having received limited health information and education [9].…”
Section: Introductionmentioning
confidence: 99%
“…The main objectives of the National Control Malaria Program (NMCP) are to reduce malaria morbidity by 40 percent and by 33 percent the malaria mortality in high-burden by 2026 compared to the 2015 baseline [6]. The vector control strategy implemented by the NMCP is mainly based on the mass deployment of long-lasting insecticidal nets (LLINs) every three years and recently by implementing indoor residual sprays (IRS) [79] in one district. In Côte d’Ivoire, the National Malaria Strategic Plan 2016–2020 has prioritized indoor residual spraying (IRS) as an additional vector control method to reduce malaria morbidity and mortality [10].…”
Section: Introductionmentioning
confidence: 99%